Exchange Rate, Stock Return, and Bond Return in Indonesia: An ARDL Approach - Ghazali Syamni; Sawitri Sawitri; Rizal Ansari; Rasyimah Rasyimah; Husaini Husaini (University of Merdeka Malang, 2022)
The purpose of this research is to investigate the relationship between the Indonesian exchange rate, stock return, and bond return. This study uses time series data in monthly frequencies from sources Thomson Reuters and Bank Indonesia during the period January 2010 to December 2020. This paper uses quantitative research by employing the Autoregression Distribution Lage (ARDL) approach to analyze the causal relationship between variables in this study. According to the results of the ARDL estimation, changes in exchange rates were inversely related to stock returns. Various findings were also found, demonstrating that changes in exchange rates were positively related to bond returns. Stock and bond returns, on the other hand, were inversely related. According to this study, when there is uncertainty in the stock market, investors would rebalance their portfolios. When investors move their money to safer places or safe havens, this is known as the